1999
DOI: 10.1002/(sici)1097-4547(19990401)56:1<99::aid-jnr13>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Stable transfection of PC12 cells with estrogen receptor (ERα): Protective effects of estrogen on cell survival after serum deprivation

Abstract: Potential protective effects of the gonadal steroid estrogen on neurons are of particular interest in aging, neurodegenerative disease, and other traumatic conditions. In this study, we examined the hypothesis that estrogen, acting through the estrogen receptor (ERalpha), can enhance neuronal cell survival in the face of serious apoptotic challenge. PC12 cells were transfected with full-length rat ERalpha cDNA and a number of stable transfectants that expressed ER mRNA and protein (PCER cells) at levels compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 37 publications
2
27
0
3
Order By: Relevance
“…Replacement with 17β-oestradiol (21 days) throughout the post-ovariectomy period reduced the number of apoptotic cells to control levels and prevented the enhancing effects of ovariectomy on Bax expression but only partially restored Bcl-2 expression. It has been shown that oestradiol reduced mRNA levels of the pro-apoptotic Bad in PC12 cells transfected with ERα (Gollapudi and Oblinger 1999). Nopparat et al (2010) have demonstrated, in the SK-N-SH dopaminergic cell line, a novel role of melatonin in protecting cells from autophagic cell death triggered by the Bcl-2/Beclin 1 pathway, by inhibiting the activation of the JNK1 (cJun amino-terminal kinase), Bcl-2 upstream pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement with 17β-oestradiol (21 days) throughout the post-ovariectomy period reduced the number of apoptotic cells to control levels and prevented the enhancing effects of ovariectomy on Bax expression but only partially restored Bcl-2 expression. It has been shown that oestradiol reduced mRNA levels of the pro-apoptotic Bad in PC12 cells transfected with ERα (Gollapudi and Oblinger 1999). Nopparat et al (2010) have demonstrated, in the SK-N-SH dopaminergic cell line, a novel role of melatonin in protecting cells from autophagic cell death triggered by the Bcl-2/Beclin 1 pathway, by inhibiting the activation of the JNK1 (cJun amino-terminal kinase), Bcl-2 upstream pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects could involve protein synthetic activity and help explain the volume changes reported by Coujard (1951). In addition, Gollapudi and Oblinger (1999a) have shown that ER-α is present in PC12 cells [neural crest derivatives that are nerve growth factor (NGF)-dependent] and that estrogens have cytoprotective (cell survival) effects that involves NGF and the antiapoptotic molecule Bcl-X L (Gollipudi and Oblinger 1999b). Furthermore, estrogens stimulate neurotransmitter levels (in CNS neurons; Gibbs et al 1994;Okamura et al 1994aOkamura et al , 1994bYuri and Kawata 1994;Dufourny and Warembourg 1999;Miller et al 1999), upregulate neuronal-nitric oxide synthase in autonomic and/or sensory nerves in the vagina (Berman et al 1998), or downregulate CGRP in sensory neurons (Moussaoui et al 1996;Duval et al 1998;Yang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation occurs via the action of endonucleases. The TUNEL method specifically labels DNA ends generated by endonuclease activity [28]. To confirm the results of DNA electrophoresis, quantification of DNA ladders was carried out by the TUNEL methods in the cells treated with 0-10,000 ng/ ml DEP for 72 hr.…”
Section: Cell Viabilitymentioning
confidence: 99%